전 복강경 술식에 의한 간 절제술에 대한 경험 - 김창균(Chang Gyun Kim); 윤유석(Yoo-Seok Yoon); 한호성(Ho-Seong Han); 신상현(Sang-Hyun Shin); 전광식(Kwang-Sik Chun); 장진영(Jin-Young Jang); 서경석(Kyung-Suk Suh); 김선회(Sun-Whe Kim); 이건욱(Kuhn Uk Lee); 박용현(Yong-Hyun Park) (Annals of surgical treatment and research, 2007)
Purpose: The aim of this study is to assess the feasibility and clinical outcomes of laparoscopic liver resection by reviewing our experience of laparoscopic liver resection performed in a single institution. Methods: We retrospectively analyzed the clinical outcome of 64 patients that had undergone laparoscopic liver resection for various liver diseases between May 2003 and June 2006. Results: The patients were composed of 36 men and 28 women, with a mean age of 56.9 years. Indications for laparoscopic liver resection included 37 cases of a tumor (20 hepatocellular carcinomas, 8 metastatic cancers and 9 benign tumors) and 25 cases of IHD stones. The surgical procedures were 19 tumorectomy cases, 24 left lateral sectionectomy cases, 15 left hepatectomy cases, 4 right posterior sectionectomy cases and 2 right hepatectomy cases. The mean surgical time was 280.3 minutes. Intraoperative transfusion was required for 18 patients (28.1%). There was one postoperative death (1.6%) due to biliary sepsis after a left lateral sectionectomy for an IHD stone. Postoperative complications developed in 9 cases (14.0%) (2 intraabdominal abscesses, 1 hematoma, 1 bile leakage, 1 ascites, 1 gastric variceal bleeding, 1 ulcer bleeding and 1 anastomosis leakage), all of which were improved by conservative management. The mean postoperative hospital stay was 11.0 days. Conclusion: Our experience shows that laparoscopic liver resection is a feasible operation and is comparable to surgery with the open method. However, a prospective com-parative study with long term follow-up is needed to confirm the equivalence of the procedures. (J Korean Surg Soc 2007;73:490-495) KCI Citation Count: 4